Accounting for managers : a skill-building approach - Treesa, Jency (Abingdon, Oxon ; New York, NY : Routledge, 2024)
"This book presents fundamental aspects of financial accounting, its basic terminology, the accounting process, and the preparation of a journal, ledger, trial balance, income statement, and balance sheet. It also introduces complex topics like tools of management accounting, sustainability reporting and financial reporting. The volume comprehensively delivers lessons and examples to build strong accounting skills guiding readers to learn how to read and analyse financial statements, and discusses the theoretical concepts followed by elaborating on the accounting process in a simple and lucid style. Numerical examples and case studies support every discussion involving a conceptual difficulty. Several charts and diagrams have been included to shed light on the finer points of the subject to make it easily comprehensible. This book would be useful to students, researchers, and teachers of financial accounting, accounting, statistics, and business management. The book would also be useful for anyone interested in learning the basic concepts of financial accounting to help them in their daily lives"--
Introduction to Accounting -- Journal -- Sub-divisions of Journal -- Ledger and Trial Balance -- Capital and revenue -- Depreciation, Provisions and Reserves -- Financial Statements -- Financial statement analysis -- Ratio Analysis -- Fund flow statement -- Cash flow statement -- Reading financial statements -- Financial Reporting -- Sustainability reporting.
Keywords: Managerial accounting; BUSINESS & ECONOMICS / Accounting / Financial; BUSINESS & ECONOMICS / Accounting / Managerial